2013
DOI: 10.1902/jop.2012.120180
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol Inhibits P. intermedia Lipopolysaccharide‐Induced Production of Nitric Oxide Through Translational Regulation in Murine Macrophages: Critical Role of Heme Oxygenase‐1‐Mediated ROS Reduction

Abstract: Background: Nitric oxide (NO) could be a potential target for the development of new therapeutic approaches to the treatment of periodontal disease because this molecule plays a significant role in the tissue destruction observed in periodontitis. In this study, the authors investigate the effect of kaempferol on the production of NO by murine macrophage‐like RAW264.7 cells stimulated with lipopolysaccharide (LPS) from Prevotella intermedia, a pathogen implicated in periodontal disease, and try to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…occurred together with ROS reduction. This is consistent with the finding that induction of HO-1 by isorhamnetin, a 3 0 -Omethylated metabolite of quercetin, 40 flavonoid kaempferol, 41 and curcumin, an anti-inflammatory agent extracted from Curcuma longae, 42 leads to a reduction in ROS production in RAW 264.7 cells. Curcumin also was found to reduce ROS levels by upregulating HO-1 expression in human retinal pigment epithelial cells.…”
Section: Discussionsupporting
confidence: 88%
“…occurred together with ROS reduction. This is consistent with the finding that induction of HO-1 by isorhamnetin, a 3 0 -Omethylated metabolite of quercetin, 40 flavonoid kaempferol, 41 and curcumin, an anti-inflammatory agent extracted from Curcuma longae, 42 leads to a reduction in ROS production in RAW 264.7 cells. Curcumin also was found to reduce ROS levels by upregulating HO-1 expression in human retinal pigment epithelial cells.…”
Section: Discussionsupporting
confidence: 88%
“…Then, an integrated in silico approach was applied to decipher the 42 targets for these active ingredients related to BSS including 27 common targets, which distinctly explained the action modes and biological processes that active ingredients achieve their synergistic and complementary curative effects. It is worth mentioning that the results from several compound-target interaction experiments by us and other groups indicated the reasonability of our integrated in silico approach4546474849505173. Subsequently, 20 signaling pathways associated with BSS treatment and prophylaxis by Danggui-Honghua were retrieved.…”
Section: Discussionmentioning
confidence: 94%
“…For example, in animal models, increased expression of HMOX1 has been shown to protect tissues and cells against ischemia-reperfusion injury, oxidative stress, inflammation and hypoxia-induced vascular stasis47. The protein HMOX1 was found to have interactions with 9 ingredients, and senkyunolide A, kaempferol and eriodictyol synergistically increase HMOX1 expression484950. In addition, the neurotoxic proinflammatory mediator PTGS2 was also connected with several active ingredients.…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al (2012) have suggested that quercetin attenuates ethanol-induced oxidative stress through a pathway which HO-1 upregulation. The second most abundant active substance in linden inflorescence, namely kaempferol, inhibits nitric oxide production and nitric oxide synthase protein expression via HO-1-mediated ROS reduction in murine macrophages (Choi et al, 2012). Although in our study the administration of hydrolyzed and non-hydrolyzed linden extract did not influenced the HO-1 gene expression we were able to identify the 18 genes which were expression targets of HO-1 (Table 4).…”
Section: Discussionmentioning
confidence: 52%